Supplementary material for "Characterization of RcgA and RcgR, two rhizobial proteins involved in the modulation of plasmid transfer" - Castellani, Lucas Gabriel (2025)
Plasmid conjugative transfer (CT) is a major mechanism of horizontal gene transfer in bacteria, facilitating genome evolution and dissemination of adaptive traits. Due to the energetic cost of CT, its regulation becomes an important process to ensure energetic balance within cells. In Rhizobium favelukesii, the plasmid pLPU83a belongs to group I-C of rhizobial plasmids, which require the transcriptional regulator TraR for CT. In well-characterized systems, TraR typically activates conjugative genes in response to quorum-sensing (QS) signals such as acyl-homoserine lactones. However, pLPU83a does not respond to these signals, raising questions about how TraR is regulated in this system. This study addresses the function of RcgA and RcgR, two proteins encoded upstream of traR on pLPU83a, whose function has previously been associated with CT modulation. Through proteomic, transcriptomic, and microscopy approaches, we show that RcgR acts as a repressor of CT, inhibiting traR expression and, therefore, the transcription of genes involved in CT, thereby reducing plasmid transfer rate. In contrast, RcgA is essential for CT but does not affect the expression of CT genes; is localized at the membrane and may play a structural role in the mating pair formation system. Functional assays revealed that the repression facilitated by RcgR is independent of the anti-activator TraM and that TraR is essential for transfer even in the absence of RcgR. These findings locate RcgA and RcgR as key elements of a new circuit that modulates rhizobial plasmid conjugation and propose a novel mechanism of TraR control in systems uncoupled from QS signaling.